A intelectualidade feminina e os saberes para professores - Grespan, Fernanda Plaza (Editora Oficina Universitária, 2022)
In search of a history of teacher training at the Normal School of Rio Grande de Sul, the author presents the trajectory of the Normal School in Porto Alegre/Rio Grande do Sul between the years 1922 - 1931, a period in which the magazine O Estúdio was published. circulated, being a differentiated print, produced by students and future teachers, where they can be considered intellectuals of a time when there were not many female writers. In this book, Fernanda Plaza Grespan seeks to understand, through the data and information contained in the magazine, the emphasis given to knowledge for teachers as subjects in the magazine, emphasizing the feminization of teaching.